PENGARUH STRUKTUR KEPEMILIKAN DAN KINERJA KEUANGAN TERHADAP AGRESIVITAS PAJAK DENGAN UKURAN PERUSAHAAN SEBAGAI VARIABEL INTERVENING - Rizki Andreani; Wirmie Eka Putra; Fitrini Mansur (J-MACC, 2025)
This study aims to determine the influence of ownership structure and financial perfomance on tax agressiveness through company size as an intervening variabel in empirical studies of sectoral companies listed on the Indonesia Stock Exchange (IDX) for the 2021-2023 period. The data used in this study is secondary data in the form of an annual report ehich is accessed through the www.idx.xom and related company websites which are used as samples and use the data colection method by way of documentation. The data analysis method used in this study is the Partial Least Square - Structural Equation Modelling (PLS-SEM) method which is component-based or variance using SmartPLS software. The results of this study show that the ownership structure through foreign share ownership and public or public ownership does not have a significant effect on tax aggressiveness. The size of company through total assets, the amount of profit, and the number of employees do not have a significant effect on tax aggressiveness. Meanwhile, financial performance through leverage and profitability has a ownership structure and financial performance against tax aggressiveness.